Delivering Person-Centered Care in Community Mental Health Programs. (November 2020) - Choy-Brown, Mimi; Stanhope, Victoria; Williams, Nathaniel; Bond, Lynden
The aim of this study was to examine the extent of and variation in person-centered care across programs within community mental health clinics. Service plans ( N = 160) from programs within eight clinics were assessed for person-centered care planning using an objective fidelity measure. Univariate statistics calculated overall fidelity to person-centered care planning and mixed-effect regression models examined person-centered care planning by program type. Overall, providers demonstrated low levels of competency in person-centered care planning. There were significant differences according to program type, with providers from assertive community treatment programs demonstrating the highest level of competency. Providers need more training and support to implement person-centered care consistently across community mental health programs. Those program types with associated fidelity measures that include person-centered care had a higher level of competence confirming the value of fidelity measurement in promoting quality services.